THE RELATIONSHIP OF MOTHER'S PERCEPTION OF IUD CONTRACEPTION WITH THEIR PARTICIPATION AS IUD ACCEPTANCE IN PUSKESMAS 1 DENPASAR SELATAN - Noriani,S.Si.T., M.Kes, Ni Ketut; Nurtini,S.Si.T.,M.Kes, Ni Made (Jurnal Riset Kesehatan Nasional, 2021)
The arge population growth without being accompanied by good quality human resources complicates efforts to increase and distribute people's welfare. Controlling the rate of population growth is pursued through the family planning program, which is expected to involve the participation of all parties in realizing the success of family planning in IndonesiaA person's actions are influenced by multiple factors, including the use of contraceptives. These factors include predisposing factors (knowledge, attitudes and other elements that exist in the individual), supporting factors, namely the availability of health facilities and reinforcing factors such as family support. The knowledge referred to above is the mother's knowledge about the use of contraception, especially its benefits in preventing pregnancyGood understanding of knowledge is expected to emerge attitudes in the form of awareness and intention to use safe and quality contraceptives (Notoatmojo, 2007). This is in accordance with research conducted by Gertler and Molyneaux (2003) cited by Syafitri (2010), more than 50% of family planning users who have good knowledge and not much different from research conducted by Sindhung (1999), as many as 60% of mothers have good knowledge of KB. So if the knowledge is good then the family planning program will be successful.The purpose of this study was to determine the relationship between the level of mother's perception of the use of IUD contraceptives in the Work Area of Puskesmas 1 South Denpasar. The methodology used in this research is cross sectional analytic. The population in this study were IUD family planning acceptors in the Work Area of Puskesmas I South Denpasar in January 2020. Sampling was carried out by incidental sampling. The data collection instrument in this study was a questionnaire. The correct information delivered from health workers can be a guide to form a person's support and interest in choosing an IUD contraception. This is in accordance with Setiadi's 2008 theory in Nurhayati's 2016 research, the role of health workers is an activity that is expected from a health worker who provides health services to the community to improve community health status optimally.Keywords: Mother's perception of IUD, Mother's participation as IUD acceptorÂ